2022
DOI: 10.3310/jnzt9406
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial scratch to increase live birth rates in women undergoing first-time in vitro fertilisation: RCT and systematic review

Abstract: Background In vitro fertilisation is a widely used reproductive technique that can be undertaken with or without intracytoplasmic sperm injection. The endometrial scratch procedure is an in vitro fertilisation ‘add-on’ that is sometimes provided prior to the first in vitro fertilisation cycle, but there is a lack of evidence to support its use. Objectives (1) To assess the clinical effectiveness, safety and cost-effectiveness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 112 publications
(511 reference statements)
0
4
0
Order By: Relevance
“…The combined data showed that endometrial scratching had no statistically significant positive effect on LBRs (risk difference (RD) 0.05; 95% CI −0.02 to 0.13; P = 0.17) ( Pluddemann and Onakpoya, 2020 ). Further data for women undergoing a first cycle confirmed no significant effect on LBR in the trial (unadjusted RR 1.04; 95% CI 0.89 to 1.21; n = 1048), and when combining the trial with published data (OR 1.03; 95% CI 0.87 to 1.22; 9 RCTs; n = 2473; I 2 = 0%) ( Metwally etal. , 2022 ).…”
Section: Resultsmentioning
confidence: 86%
“…The combined data showed that endometrial scratching had no statistically significant positive effect on LBRs (risk difference (RD) 0.05; 95% CI −0.02 to 0.13; P = 0.17) ( Pluddemann and Onakpoya, 2020 ). Further data for women undergoing a first cycle confirmed no significant effect on LBR in the trial (unadjusted RR 1.04; 95% CI 0.89 to 1.21; n = 1048), and when combining the trial with published data (OR 1.03; 95% CI 0.87 to 1.22; 9 RCTs; n = 2473; I 2 = 0%) ( Metwally etal. , 2022 ).…”
Section: Resultsmentioning
confidence: 86%
“…Metwally et al. 55 conducted a systematic review in 2022 that included the effect of scratching in women undergoing their first IVF cycle. Their review included 12 studies.…”
Section: Discussionmentioning
confidence: 99%
“…More conclusive evidence of the effects of ESI is required for practitioners who treat all types of patients undergoing IVF. Metwally et al 55 conducted a systematic review in 2022 that included the effect of scratching in women undergoing their first IVF cycle. Their review included 12 studies.…”
Section: Comparison Of Our Study With Existing Literaturementioning
confidence: 99%
“…However, the studies came to inconsistent conclusions. Several studies show an enhanced implantation rate after scratching [ 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 ], while there are also several studies that could not or barely show significant differences due to scratching [ 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 ...…”
Section: Clinical Significance In Reproductive Medicinementioning
confidence: 99%